IMPLEMENTASI MODEL DECISION DALAM PENENTUAN PEGAWAI TERBAIK PADA BMKG MALIKUSSALEH MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING - Veri Ilhadi; Mutammimul Ula (Universitas Trilogi, 2023)
The decision support system in the decision model is something that is needed in every institution, both private and government, this requires a high level of accuracy in the process. Employee performance appraisal is also a matter of great concern with several standard criteria. decision models can be used in the assessment process needed in a decision making. The model used is Simple Additive Weighting (SAW) which is carried out with the provisions of the criteria and also weighting. This website was built using the Python programming language and Flash (library). The research methodology is based on the BMKG Malikussaleh assessment system which still uses manual calculations, namely the admin calculates one by one based on an assessment. The methodology of this research is to include the overall employee criterion values which will be processed using the SAW model and the results displayed on the web to determine the ranking value of the BMKG malikussaleh employees. Furthermore, the results of the best employee performance assessment based on the criteria selected Siswanto who was in first place the best employee